Developing Certificate Programs to Increase Departmental Student Enrollment - Jennifer B Lemoine; Anita Hazelwood (Academic Chairpersons Conference Proceedings, 2023)
Colleges/universities must think of innovative methods for attracting students to their campuses. Certificate programs have proven to do this. This presentation will address the decisions to offer certificate programs, the advantages and disadvantages for doing so, and will take participants through the step-by-step process of implementing these types of programs.
Keywords: Certificate programs; trends; enrollment; certificates; innovation